An Investigation of Static and Dynamic Mechanical Properties of Eco-Friendly Textile PLA Composites Reinforced by Flax Woven Fabrics - Amna Pervaiz; Farooq Azam; Ahsan Ahmad; Faheem Ahmad; Sheraz Ahmad; Tehseen Ullah; Yasir Nawab; Khubab Shaker (International Journal of Polymer Science, 2024)
The use of sustainable natural fibers as reinforcement in polylactic acid (PLA) composites offers a promising approach to developing environmentally friendly and renewable composite materials. This research article explores the impact of weave designs on various mechanical properties of fiber-reinforced polymeric composite (FRPC) laminates. Four different weave designs, including 1/1 plain, 2/2 matt, 4/1 satin, and 3/1 twill, were developed using flax yarn obtained from the Linum usitatissimum plant. These weave designs were incorporated into composites by wrapping the flax yarn with PLA filament as the matrix, followed by compression molding. The study examines the static and dynamic mechanical properties of the subsequent flax/PLA composites, including flexural strength, Charpy strength, tensile strength, and viscoelastic characteristics like damping factor, loss, and storage modulus. The plain 1/1–reinforced composite exhibits superior tensile strength (12 MPa), tensile modulus (9800 MPa), and flexural properties (29 MPa) due to the higher number of intersection points in the weave design, while in the case of impact strength (6.7 kJ/m2), satin structure-reinforced composite showed superior properties due to higher float length of warp yarns and lower intersection points in the weave structure.